2021
DOI: 10.1177/13524585211018116
|View full text |Cite
|
Sign up to set email alerts
|

Altered anterior default mode network dynamics in progressive multiple sclerosis

Abstract: Background: Modifications in brain function remain relatively unexplored in progressive multiple sclerosis (PMS), despite their potential to provide new insights into the pathophysiology of the disease at this stage. Objectives: To characterize the dynamics of functional networks at rest in patients with PMS, and the relation with clinical disability. Methods: Thirty-two patients with PMS underwent clinical and cognitive assessment. The dynamic properties of functional networks, retrieved from transient brain … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…The 13 extracted spatial maps represented in each iCAP correspond to well-known resting state networks and were reminiscent of common task-related and cognitive networks typically observed in fMRI studies (Van Den Heuvel and Pol, 2010). They also correspond to iCAP networks identified in previous studies (Bommarito et al, 2021; Piguet et al, 2021; Siffredi et al, 2021; Zöller et al, 2019). Specifically, the obtained networks included sensory-related networks, i.e., sensori-motor/auditory, primary and secondary visual; higher level cognitive network, i.e., the fronto-parietal, frontal and fronto-temporal left and right networks; and default-mode network (DMN) decomposed into precuneus/posterior DMN and posterior DMN.…”
Section: Resultssupporting
confidence: 84%
“…The 13 extracted spatial maps represented in each iCAP correspond to well-known resting state networks and were reminiscent of common task-related and cognitive networks typically observed in fMRI studies (Van Den Heuvel and Pol, 2010). They also correspond to iCAP networks identified in previous studies (Bommarito et al, 2021; Piguet et al, 2021; Siffredi et al, 2021; Zöller et al, 2019). Specifically, the obtained networks included sensory-related networks, i.e., sensori-motor/auditory, primary and secondary visual; higher level cognitive network, i.e., the fronto-parietal, frontal and fronto-temporal left and right networks; and default-mode network (DMN) decomposed into precuneus/posterior DMN and posterior DMN.…”
Section: Resultssupporting
confidence: 84%
“…DMN and visual dynamics were anti-correlated in HC, but this was lost in CI d’Ambrosio et al, 2020 62 people with RRMS 65 HC People with CI MS had reduced TVC between subcortical network and DMN compared to CP MS, and spent less time in a connectivity state characterized by high FC strength Rocca et al, 2020 50 people with CIS 13 HC People with CIS exhibited decreased TVC in networks hit by the clinical attack, and increased FC dynamism over two-years of follow-up Lin et al, 2020 25 people with RRMS 41 HC In people with MS, higher stationary and dynamic interhemispheric FC between homologous regions was associated with higher scores at different neuropsychological tests Cordani et al, 2021 41 people with MS 46 HC Increased TVC in sensorimotor and cognitive networks was found in people with MS following two weeks of action-observation training and, to a lesser extent, following control training Tijhuis et al, 2021 35 people with RRMS 19 HC People with MS had higher global TVC compared to HC; in MS, TVC strength between the basal ganglia and DMN explained the presence/absence of fatigue Hidalgo de la Cruz et al, 2021 128 people with MS 40 HC People with MS exhibited overall lower TVC, but also marginal increase of TVC in sensorimotor and cognitive networks vs HC in middle/highly connected states. TVC abnormalities were more severe in progressive MS and in CI MS people Bommarito et al, 2021 22 people with progressive MS 25 HC Reduced TVC in the anterior DMN and increased TVC in the executive control network was found in people with progressive MS compared to HC. Decreased anterior DMN TVC explained cognitive disability Schoonheim et al, 2021 278 people with MS 41 HC SPMS showed cerebellar connectivity changes, compared to RRMS and HC, including lower static FC in the fronto-parietal network and DMN, and higher TVC in dorsal and ventral attention, DMN and deep grey matter networks.…”
Section: Spatiotemporal Profiles Of Functional Reorganization: Time-v...mentioning
confidence: 88%
“…( Schoonheim et al, 2021 ) When looking at people with progressive MS, mixed patterns of TVC abnormalities were detected. Overall, decreased TVC in the DMN, ( Hidalgo de la Cruz et al, 2021 , Bommarito et al, 2021 ) as well as in sensorimotor and visual networks ( Hidalgo de la Cruz et al, 2021 ) was found in progressive MS. However, more severe disability in people with MS was also characterized by abnormally high TVC in frontal/attention networks ( Hidalgo de la Cruz et al, 2021 ) and between cerebellum and DMN, attention and basal ganglia networks, ( Schoonheim et al, 2021 ) suggesting a maladaptive mechanism.…”
Section: Spatiotemporal Profiles Of Functional Reorganization: Time-v...mentioning
confidence: 92%
“…To quantify how dynamically the network is fluctuating, most studies have looked at the variability of a network measure of interest, such as FC (e.g. ( Bommarito et al, 2021 , Leonardi et al, 2013 , Lin et al, 2018 )) or advanced measures (e.g. ( Zhou et al, 2016 )).…”
Section: Time-varying Network: Are Brain Dynamics Altered In Ms?mentioning
confidence: 99%